2010
DOI: 10.5195/ijt.2010.6055
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation in Scotland: Current Initiatives and Recommendations for Future Development

Abstract: Rehabilitation services are set to become central to modern health care systems as they strive to support an increasingly ageing population to live as independently as possible, while maintaining quality services. Alternative service delivery options such as telerehabilitation may assist in meeting the growing demand for services and many countries are exploring the potential use of telerehabilitation within their health care systems. The Scottish Centre for Telehealth commissioned an independent scoping study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…31 The potential for telehealth to reduce waiting times for rural patients and assist in meeting the rising demand for specialist rehabilitation services was also highlighted in the review by Hill. 25 Attendance rates were also improved in SAC-T, possibly due to the presence of a local physiotherapist at the preliminary consultation. The new patient-to-review ratio (7.3:1) and the new patient discharge rate (64%) in SAC-T were comparable with SAC-O.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 The potential for telehealth to reduce waiting times for rural patients and assist in meeting the rising demand for specialist rehabilitation services was also highlighted in the review by Hill. 25 Attendance rates were also improved in SAC-T, possibly due to the presence of a local physiotherapist at the preliminary consultation. The new patient-to-review ratio (7.3:1) and the new patient discharge rate (64%) in SAC-T were comparable with SAC-O.…”
Section: Discussionmentioning
confidence: 97%
“…This research contributes to the growing body of evidence that telehealth is cost-effective in comparison to face-to-face consultations. Evidence of cost-savings in favour of telehealth has been demonstrated in teleoncology, 22 pulmonary rehabilitation 25 and speech pathology for adults with dysarthria, 26,27 as well as children with hearing loss. 28 The principal contribution to cost savings was avoided travel by either patients or clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 19 articles looked at health care provider cost, patient cost, or costs incurred by both. This comprised 5 RCTs [25,26,41,60,71], 3 systematic reviews [73,75,104], 2 nonsystematic reviews [54,91], 1 retrospective study [27], 1 case-control study [78], 1 service report [96], 3 pilots [12,43,55], and 3 protocols [38,68,106]. Nearly all of the studies reported higher costs for health care providers, including all RCTs.…”
Section: Costmentioning
confidence: 99%
“…A pilot study of teleconsultations in a rural dentistry setting found that up to ÂŁ270 per patient appointment could be saved by the health service if it adopted teleconsultations to allow rural patients access specialist services [55]. In Scotland, a report on telehealth services found teleconsultations for a 10-week rehabilitation course could be delivered for 3% to 10% of the cost associated with an outreach model (where the therapist travels) or a centralized model (where the patient travels), with the savings primarily being delivered through reduced travel costs [91].…”
Section: Costmentioning
confidence: 99%
“…Telerehabilitation practices are examined from the viewpoints of an individual taking part in the ISBN: 978-989-8704-19-1 © 2020 rehabilitation, the rehabilitation service provider and their employees, and the municipalities responsible for offering rehabilitation services. Testing of new telerehabilitation practices include an examination focusing on their costs and benefits on monetary terms, contributing thus to an ongoing scientific debate on the economic aspects related to healthcare (Hill, 2010, Tousignant et al, 2015. Our economic analysis is based on the cost-benefit analysis method presented by Oxenburgh and Marlow (2005) and in this article we present the categorization of the costs related to telerehabilitation and calculate different scenarios for those cost elements in which we consider variation exists.…”
Section: Introductionmentioning
confidence: 99%